Parenting Style to Support The Cognitive Development of Early Childhood - M. Fadlillah; Ratna Pangastuti (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
Parents are responsible for the parenting of their children. The parenting style has a very big effect on child development. However, not all types of parenting styles can improve child cognitive competence. This is due to parents’ limited understanding of parenting styles. This study aims to reveal and analyze the role of parenting styles to support the cognitive development of early childhood. This research uses a qualitative method with a library study approach. Data obtained through the study and analysis of literature related to parenting, such as scientific articles and books. The result of literature reviews show that parenting styles play a very important role in the cognitive development of early childhood. The most appropriate and dominant parenting style in optimizing the cognitive competence of early childhood is the authoritative style. This style has the highest demand and response, and it prioritizes warmth, encouragement, and care about early childhood.The authoritative style is believed to be suitable for the need and characteristics of early childhood cognitive development. Keywords: Parenting Style, Cognitive Development, Early Childhood